Estimating Bargaining-related Tax Advantages of Multinational Firms - Peter H. Egger; Nora M. Strecker; Benedikt Zoller-Rydzek (Center for Economic Studies and ifo Institute (CESifo), 2018)
Bargaining power may explain the tax differences between multinational and national enterprises beyond MNEs' profit shifting. Larger firms (mostly MNEs) are more valuable for tax authorities for various reasons. In threatening relocation, larger firms extract greater deductions, resulting in a regressive ETR schedule and lower ETRs for size-related reasons. MNEs face lower relocation costs than NEs, which enhances their bargaining position. Using French firm-level data and entropy balancing, we find that the regressivity of the French tax schedule reduces MNEs' ETRs by 2.52 percentage points (size effect), while their relocation threat leads to a 3.58 percentage point reduction.
Keywords: H25; H26; F23; C21; 330; profit taxation; multinational firms; entropy balancing